GAME QUIZ INTERAKTIF BERBASIS CANVA: MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATERI PERKEMBANGBIAKAN HEWAN - Sari, Wulan Indah; Nuruddin, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this educational research is to produce an interactive quiz game leraning media product using the canva application that is suitable and effective for use in elementary school science (IPA) learning. This product is designed to support learning so that it can strengthen student’s learning motivation and leaning outcomes can be achieved. This study used the Research and Development (R&D) method with the ADDIE (Analyze, Design, Development, Implementation, Evaluation) model. A result showed that the canva based interactive quiz game media was categorized as feasible based on the material expert test (85.65%) an material expert test (96%). While based on the result of the student questionnaire, it can can be concluded that interactive quiz game are effective in increasing student learning motivation, with a trial test data of 87.79%. from these two point it can be inferred that interactive quiz games are very worthy and effective increasing student learning motivation in animal reproduction material in elementary school.